2023
DOI: 10.3390/agronomy13010206
|View full text |Cite
|
Sign up to set email alerts
|

Pelleting of Physical Dormancy Small-Seeded Species in Astragalus sikokianus Nakai

Abstract: Astragalus sikokianus is a rare Japanese perennial of the seashore that was reported to be extinct in the wild. The small seed size and deep dormancy of A. sikokianus make it difficult for direct seeding restoration in aspects of seed handling, transport, planting, and seedling establishment. For the large-scale economic restoration of dormant small-seeded species, seed pelleting combined with the breaking of dormancy was studied. Physiological (prechilling and plant hormones) and physical (hot water, hydrochl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Our study found that seeds whose cover is hard need a sufficient period of time from scratching, whether by soil texture or by mechanical factors such as scarification papers or by sulfuric acid, in order to break the dormancy and free the embryo, of course by receiving a sufficient amount of water for growth, and that treating seeds with mechanical scratching has an effective role in breaking the tough seed wall, and then this scratching will help the seed germinate for a new plant, and this is consistent with the study [14] that mechanical scratching helps the seed to quickly absorb water by embryo. There are layers around the seeds that prevent water permeability and access to the embryo to provide its need for growth, and in several experiments, the effectiveness of sulfuric acid has been proven to break down the hard wall of the seed of plant species and thus grow effectively [5,10]. The varying degrees of incubation is a prerequisite for studying and knowing the optimal degree of seed growth for a new plant, and we found that A.spinosus seeds can grow efficiently in 22 and 25 °C as when treated with scarification paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that seeds whose cover is hard need a sufficient period of time from scratching, whether by soil texture or by mechanical factors such as scarification papers or by sulfuric acid, in order to break the dormancy and free the embryo, of course by receiving a sufficient amount of water for growth, and that treating seeds with mechanical scratching has an effective role in breaking the tough seed wall, and then this scratching will help the seed germinate for a new plant, and this is consistent with the study [14] that mechanical scratching helps the seed to quickly absorb water by embryo. There are layers around the seeds that prevent water permeability and access to the embryo to provide its need for growth, and in several experiments, the effectiveness of sulfuric acid has been proven to break down the hard wall of the seed of plant species and thus grow effectively [5,10]. The varying degrees of incubation is a prerequisite for studying and knowing the optimal degree of seed growth for a new plant, and we found that A.spinosus seeds can grow efficiently in 22 and 25 °C as when treated with scarification paper.…”
Section: Discussionmentioning
confidence: 99%
“…Seeds may not germinate despite the availability of suitable conditions for germination and despite their effectiveness (viable) and can be stimulated to germinate by several different parameters such a type of seed is called dormant seeds [4]. The seeds of the genus Astragalus have seed dormancy due to the hard seed coat, but they have great potential to break this dormancy and these varies depending on many factors, including plant environments as well as depending on different plant species [5]. It is reported that acid treatment is considered an effective method of enhancing seed germination for plant species in which dormancy is caused by the hardness of the seed coat [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%